A Pareto-efficient market-clearing mechanism for shared-mobility systems. (1st January 2014) - Le Vine, Scott
Shared-mobility services facilitate distinctive forms of personal mobility, and their pay-as-you-go business model has been shown to offer substantial benefits relative to use of privately-owned cars. Such systems in general operate one of two business models, in one case where customers make advance reservations and the other in which use is spontaneous and cannot be reserved with any certainty. This paper proposes a market-clearing mechanism that draws on the strengths and mitigates the weaknesses of each of these two prevailing operating models, by allowing reservations (the right to use the service at a particular time and place in the future) to be traded in a futures market. We show that there is a revenue-positive role for the market-maker of the secondary-exchange market as well as for investors in shared-mobility futures. Introducing a secondary exchange market is Pareto efficient in that shared-mobility services are allocated to customers on the basis of maximum willingness-to-pay rather than first-come-first-served. Finally, from the point of view of each individual customer there would be a step-change in the reliability of accessing shared-mobility vehicles when and where needed, which can be expected to increase overall demand for the service.